(untitled) (UNIHumanitas, 2013)
This essay intends to propose some elements for the construction of an ethno-education for Indigenous Peoples as subjects-objects of knowledge that shape reality in relation to “others” and not in isolation: each of them contains a network of relationships with other subjects-objects, which depend on an attributed meaning. Ethnodeducation challenges us to think differently and to allow indigenous people to develop an education from their own culture; through interculturality, freeing them from an education of subjugation by mestizos and/or Paraguayans. At the end it proposes roles of the School in the Indigenous Community for an intercultural ethno-education.